A diubiquitin-based photoaffinity probe for profiling K27-linkage targeting deubiquitinases. Issue 73 (31st August 2017) - Tan, Xiao-Dan; Pan, Man; Gao, Shuai; Zheng, Yong; Shi, Jing; Li, Yi-Ming
Abstract : We report a novel aryl-azide-based photoaffinity diubiquitin probe for profiling K27-linkage targeting DUBs in high selectivity and sensitivity. Abstract : K27-linkage poly-ubiquitination plays important roles in DNA damage repair and autoimmunity. Identification of K27-linkage targeting deubiquitinases (DUBs) is essential for understanding their regulatory mechanisms. Here we report an aryl-azide-based photoaffinity diubiquitin (diUb) probe for profiling K27-linkage targeting DUBs. This probe shows high selectivity and sensitivity towards K27-linkage DUBs in vitro . It can also be used in cell lysate for identifying and probing K27-linkage targeting DUBs in real proteomes. Our work suggests that the photoaffinity-based strategy may provide a new useful approach for the construction of other isopeptide linkage targeting DUB probes.